South Africa’s Rural Development Strategy, its Application and Theoretical Underpinnings: using the application of the CRDP at Muyexe Village as a Reflector - Manganyi, Kenneth (University of the Witwatersrand, Johannesburg, 2024)
Rural development in South Africa has been a key component of economic strategy since 1994. However, evaluation by both the government and outside actors reveals limited success in set targets. Integrated development, sustainability and community participation have been its key concepts, with land reform, infrastructure investment, skills development, provision of necessities and job creation as some of its important tools. The CRDP was piloted at Muyexe Village in 2009, a period when South Africa was still reeling from the GEAR strategy. As a contribution to the continuous assessment, this report is an enquiry about the content of the rural development programme and its application, and how these have been influenced by the theoretical underpinnings of the country’s macroeconomic policy choices. Reflecting on the Muyexe CRDP pilot, the report explores the theoretical anchoring of South Africa’s rural development strategy, design, and implementation. This is done by evaluating the literature on economic development, academic and official publications on South Africa’s post-apartheid macroeconomic posture, documentation on the design and implementation of the rural development programme and a case study at Muyexe village with information also collected from participants in the CRDP pilot projects, government officials and leaders of comparative communities using questionnaires, interviews and observations.
A research report submitted in fulfillment of the requirements for the Master of Commerce, In the Faculty of Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Rural Development; CRDP; Theoretical Underpinnings; SDG-11: Sustainable cities and communities